The Potential of Collective Impact: Moving the Work of Literacy Coalitions Forward - Terry S. Atkinson; Kimberly L. Anderson (The University of Alabama, 2022)
Review of the book: Frank Ridzi and Margaret Doughty, Does Collective Impact Work? What Literacy Coalitions Tell Us. Lanham, MD: Lexington Publishing, 2017, 261 pages. ISBN: 978-1-498508-45-2.